(untitled) - Trump, Donald (New York, 2015)
In this book (previously published as Crippled America), we’re going to look at the state of the world right now. It’s a terrible mess, and that’s putting it mildly. There has never been a more dangerous time.
Keywords: Chính trị và chính phủ,Politics and government; Hoa Kỳ,United States